Peranan produk simpanan perbankan syariah dalam masyarakat - Ripai, Muhamad Tamam; Yuwafi, Hamdan (Maliki Interdisciplinary Journal, 2024)
The purpose of writing this article is to be useful, help readers understand the material contained in it, and create a sense of trust in Islamic banking through the processes carried out by Islamic banks. Islamic banking is banking that applies Islamic principles in the application process. Islamic banking has advantages such as flexible timing and non-interest transactions. Islamic banking presents several products, including deposit products, including current accounts, savings, and deposits. In the application of current accounts and savings, one must use a wadi’ah and mudharabah contract, but for deposits, only mudharabah is allowed. Wadi’ah current accounts and savings are deposits from customers in the form of savings accounts. Deposits themselves are deposit products whose withdrawals cannot be made at any time in accordance with the initial agreement. What is meant by mudharabah and wadi’ah contracts is that the application process avoids usury and other prohibitions from Islam. The method for obtaining data and information is a literature review. So the results of the research obtained are Islamic banking using Islamic principles, which have advantages such as flexible time and non-interest by presenting Islamic savings products consisting of current accounts, savings, and deposits. This can be a solution for people to invest without violating Islamic Sharia.